2017
DOI: 10.1016/s1473-3099(16)30517-5
|View full text |Cite
|
Sign up to set email alerts
|

Health-care-associated infections in neonates, children, and adolescents: an analysis of paediatric data from the European Centre for Disease Prevention and Control point-prevalence survey

Abstract: Background: In 2011/2012, the European Centre for Disease Prevention and Control

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
124
4
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(153 citation statements)
references
References 25 publications
(15 reference statements)
5
124
4
3
Order By: Relevance
“…Gram-negative pathogens are of particular concern as they account for a substantial portion of HAIs in the NICU and are associated with high morbidity and mortality. 1,14,22 In the current study, we did not observe a significant increase in the proportion, rate, or hazard of gram-negative bacilli infections with mupirocin treatment. In contrast, Perez-Fontan et al 23 previously reported an increase of gram-negative infections with nasal mupirocin use in adult peritoneal dialysis patients.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…Gram-negative pathogens are of particular concern as they account for a substantial portion of HAIs in the NICU and are associated with high morbidity and mortality. 1,14,22 In the current study, we did not observe a significant increase in the proportion, rate, or hazard of gram-negative bacilli infections with mupirocin treatment. In contrast, Perez-Fontan et al 23 previously reported an increase of gram-negative infections with nasal mupirocin use in adult peritoneal dialysis patients.…”
Section: Discussioncontrasting
confidence: 56%
“…13 Decolonization is a strategy to prevent S. aureus by reducing the bioburden of skin colonization that may otherwise increase risk of subsequent S.aureus infection or transmission. In neonatal intensive care units (NICUs), decolonization primarily has been used to control epidemic and endemic methicillin-resistant S. aureus (MRSA).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Neonates are especially susceptible to episodes of LOS due to an immature immune system, and they frequently require invasive devices, including central lines, to deliver life-saving medications and parenteral nutrition. The use of such devices significantly increases the risk of infection, and central line-associated bloodstream infections (CLABSIs) are an important cause of LOS 4. While there is some uncertainty regarding the impact of CLABSIs on neurological outcomes,1 recent evidence suggests that reductions in coagulase-negative staphylococcal (CoNS) infections may reduce cognitive disability in preterm infants 5…”
Section: Introductionmentioning
confidence: 99%
“…Staphylococcus aureus remains one of the principal causes of HAI in children (8)(9)(10)(11). In S. aureus, the smr gene and the qacA/B gene complex have been associated with elevated MICs and minimum bactericidal concentrations (MBCs) of CHG. A number of investigators have discovered an increase in the incidence of organisms bearing these genes following widespread use of CHG in hospital units (12)(13)(14) and, more rarely, following exposure to CHG outside the hospital setting (15,16).…”
mentioning
confidence: 99%